2017
DOI: 10.21307/jofnem-2017-081
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Signals of Vector Beetle Facilitate the Prevalence of a Native Fungus and the Invasive Pinewood Nematode

Abstract: Small heat shock proteins (sHSP) are ubiquitously found in all organisms, and with other heat shock proteins (HSP) such as HSP60, HSP70, HSP90, HSP100 made up the molecular chaperone family. They are involved in a wide range of biological processes which include among others cell resistance to biological and environmental stress conditions. In this study, we show by western blotting that CeHSP17, an sHSP of Caenorhabiditis elegans, is significantly induced by high temperatures. Furthermore, in response to meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 70 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Our work and that of others have shown that the combined temperature and certain metal exposure could induce toxicity and stress protein response in human endothelial cells, Caenorhabditis elegans , Mytilus galloprovincialis , Larimichthys crocea , Triticum aestivum L . It has also been proposed that the heterologous overexpression of both prokaryotic and eukaryotic sHSPs could enhance organism tolerance and adaptation to stress conditions .…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our work and that of others have shown that the combined temperature and certain metal exposure could induce toxicity and stress protein response in human endothelial cells, Caenorhabditis elegans , Mytilus galloprovincialis , Larimichthys crocea , Triticum aestivum L . It has also been proposed that the heterologous overexpression of both prokaryotic and eukaryotic sHSPs could enhance organism tolerance and adaptation to stress conditions .…”
Section: Introductionsupporting
confidence: 56%
“…[18,19] In vitro studies have demonstrated that AgsA formed fibrils and possesses strong chaperone-like activity at elevated temperature. [20] Our work and that of others have shown that the combined temperature and certain metal exposure could induce toxicity and stress protein response in human endothelial cells, [21] Caenorhabditis elegans, [22,23] Mytilus galloprovincialis, [24] Larimichthys crocea, [25] Triticum aestivum L. [26] It has also been proposed that the heterologous overexpression of both prokaryotic and eukaryotic sHSPs could enhance organism tolerance and adaptation to stress conditions. [19,[27][28][29][30] However, literature describing the combined effects of heavy metals and temperatures, and the heat shock proteins response mainly focused on aquatic organisms [8,31] and still are relatively scarce on E. coli cells.…”
mentioning
confidence: 99%
“…Heat shock proteins are stress-responsive proteins and play an important role in protecting cells from elevated environments. CeHSP17 was significantly up-regulated by cadmium and zinc in wild-type C. elegans [36]. In transgenic Arabidopsis, PfHSP17.2 showed a higher resistant ability under heat, cold and salt stresses [37].…”
Section: Stress Induced Oxidative Injuries and Inhibited Photosyntmentioning
confidence: 96%
“…The newly eclosed beetle should have a maturation feeding in healthy trees. The nematode then departs from the spiracles driven by CO 2 enhanced by feeding behavior and invades new healthy trees via the feeding wounds 14 , 15 , thus starting a new cycle of infection, propagation and dispersal. While the chemical signals among the symbiosis have been well characterized, the molecular mechanism of the chemical communications remains elusive.…”
Section: Background and Summarymentioning
confidence: 99%